A Novel Prognostic Signature Based on Ferroptosis-Related Genes Predicts the Prognosis of Patients With Advanced Bladder Urothelial Carcinoma - Li, Xiaoqi; Huang, Junting; Chen, Ji; Zhan, Yating; Zhang, Rongrong; Lu, Enze; Li, Chunxue; Zhang, Yuxiao; Wang, Yajing; Li, Yeping; Zheng, Jianjian; Geng, Wujun (Frontiers in Oncology, 2021)
Bladder cancer (BC) is a highly heterogeneous disease, and the prediction of prognosis of Bladder Urothelial Carcinoma (BLCA), the main subtype of BC, is difficult. Ferroptosis is a newly discovered iron-dependent cell death pathway, induced by sorafenib. Ferroptosis regulation is a potential target for tumor therapy. However, the utility in prognosis of ferroptosis-related genes (FRGs) in BLCA remains uncertain. mRNA expression profiles and related clinical data from BLCA patients were obtained from the TCGA and GSE13507 databases. In the TCGA cohort, we identified 23 differentially expressed genes (DEG) associated with overall survival (OS) using univariate Cox analysis (all adjusted P <0.05). LASSO regression analysis was used to construct a multi-gene signature. Data from BLCA patients in the GSE13507 cohort were used for verification. Patients were divided into two risk groups using the median risk score generated by the newly-constructed 8-gene signature. Patient OS in the high-risk group was significantly lower than in the low-risk group. In the multiple Cox regression analysis, this risk score was an independent predictor of OS (HR>1, P<0.05). The predictive utility of the signature was demonstrated using receiver operating characteristic (ROC) curve analysis. In the TCCA cohort, most of the FRGs (51.4%) exhibited differential expression between BLCA and adjacent normal tissues. Functional analysis indicated pathways related to immunity were abundant, and the immune status between the two groups was different. We demonstrate that prognosis of BLCA can be predicted using our novel ferroptosis-related gene signature. Targeting ferroptosis has potential for treating BLCA.